2003
DOI: 10.1067/mtc.2003.117
|View full text |Cite
|
Sign up to set email alerts
|

Aortic root replacement with Freestyle stentless valve for complex aortic root infection

Abstract: ortic valve replacement in the presence of infectious endocarditis with an aortic annular abscess, aortic root destruction, and left ventricular-aortic discontinuity, remains a formidable surgical challenge. Early diagnosis and surgical intervention can be lifesaving. [1][2][3] Radical de´bridement of infected tissues and reconstruction of the left ventricular outflow tract are fundamental tenets of treatment. However, the choice of valve substitute remains one of the most contentious subjects in the managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…21 Several authors have reported good outcomes for AVR in patients with PVE and aortic root abscess using a Freestyle stentless valve. 9,13,22 Because the handling qualities and performance of a Freestyle valve are similar to those of a homograft, they recommend the use of a Freestyle valve. 13,22 A composite graft or Freestyle stentless valve can serve as a good alternative to a homograft for aortic root replacement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…21 Several authors have reported good outcomes for AVR in patients with PVE and aortic root abscess using a Freestyle stentless valve. 9,13,22 Because the handling qualities and performance of a Freestyle valve are similar to those of a homograft, they recommend the use of a Freestyle valve. 13,22 A composite graft or Freestyle stentless valve can serve as a good alternative to a homograft for aortic root replacement.…”
Section: Discussionmentioning
confidence: 98%
“…9,13,22 Because the handling qualities and performance of a Freestyle valve are similar to those of a homograft, they recommend the use of a Freestyle valve. 13,22 A composite graft or Freestyle stentless valve can serve as a good alternative to a homograft for aortic root replacement. However, because prosthetic valve infection does not usually extend to the sinus of Valsalva or the coronary ostium in most patients with PVE complicated with aortic root abscess, 2-9,12-15,16-19,21-25 we do not believe that aortic root replacement is always necessary.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sakaguchi et al 7 successfully treated methicillinresistant Staphylococcus aureus-induced prosthetic valve endocarditis using the Freestyle valve. Fukui et al 15 reported that the Freestyle was implanted in five patients with complex aortic root infection. Muller et al 16 described their experience with xenograft reconstruction of the aortic root and the left ventricular outflow tract using the Freestyle bioprosthesis in 10 consecutive patients with severe destructive endocarditis.…”
Section: Commentsmentioning
confidence: 98%
“…Three of those five patients had prosthetic valve endocarditis. [7] Medtronic Freestyle aortic root bioprosthesis is a lifesaving choice in the treatment of aortic root endocarditis especially in countries like ours, where aortic homografts are not widely available. It is the valve type of choice in the surgical treatment of destructive aortic root endocarditis because of its wide availability, minimal non biologic content, anatomy like native aorta, excellent geometrical compatibility, optimum hemodynamical performance, no hemodynamic and structural deterioration in 10 year results and low rate of infectious complications.…”
Section: Discussionmentioning
confidence: 99%